Tropical forests : exploitation, conservation and management. - Ramakrishnan, P.S. (1992)
Points out that deforestation in the tropics is essentially a human problem, and a narrow-based forestry initiative alone cannot tackle it. A broader-based interdisciplinary approach will facilitate the sharing of knowledge arising out of the three major commponents of the management strategy, viz. sivicultural factor, ecological factor, and social and economic factor.